2006
DOI: 10.1093/cercor/bhl103
|View full text |Cite
|
Sign up to set email alerts
|

Better Memory and Neural Efficiency in Young Apolipoprotein E  4 Carriers

Abstract: The apolipoprotein E (APOE) e4 allele is the major genetic risk factor for Alzheimer's disease, but an APOE effect on memory performance and memory-related neurophysiology in young, healthy subjects is unknown. We found an association of APOE e4 with better episodic memory compared with APOE e2 and e3 in 340 young, healthy persons. Neuroimaging was performed in a subset of 34 memory-matched individuals to study genetic effects on memory-related brain activity independently of differential performance. E4 carri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
219
3
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 238 publications
(241 citation statements)
references
References 72 publications
18
219
3
1
Order By: Relevance
“…23,24,25 Positron emission tomography (PET) studies have consistently shown resting glucose metabolism reduction in healthy young and middleaged APOE ε4-carriers in brain regions known to be affected by AD pathology, such as the parietal, temporal and prefrontal cortices. 12,13 Taskbased functional magnetic resonance imaging (fMRI) studies have been less consistent, showing increased 11,14,15 , decreased 26,27 or even no difference 28 in task-related BOLD signal between healthy APOE ε4-carriers and non-carriers.…”
Section: Introductionmentioning
confidence: 99%
“…23,24,25 Positron emission tomography (PET) studies have consistently shown resting glucose metabolism reduction in healthy young and middleaged APOE ε4-carriers in brain regions known to be affected by AD pathology, such as the parietal, temporal and prefrontal cortices. 12,13 Taskbased functional magnetic resonance imaging (fMRI) studies have been less consistent, showing increased 11,14,15 , decreased 26,27 or even no difference 28 in task-related BOLD signal between healthy APOE ε4-carriers and non-carriers.…”
Section: Introductionmentioning
confidence: 99%
“…Filbey et al (18) reported greater activation in 8 APOE 4-carriers compared with 8 noncarriers in medial frontal and anterior cingulate areas using a working memory paradigm. Mondadori et al (17) reported reduced activation with an associative learning paradigm in 13 4-carriers relative to 11 2-carriers and 10 3-homozygotes. Both studies therefore suggest that the APOE genotype influences brain functions even early in adulthood.…”
mentioning
confidence: 99%
“…Thus far, reports of structural and functional effects of the APOE 4 allele in young adults are limited (17)(18)(19)(20). Only 2 small fMRI studies have tested for early life associations of the APOE polymorphism with changes in brain function.…”
mentioning
confidence: 99%
“…The 354 volunteers were university students and employees/trainees recruited at the university of Zurich and via advertisements in local newspapers. The 81 subjects already participated in two functional magnetic resonance imaging studies that investigated brain activity elicited by memory tasks between different apolipoprotein E genotypes (Mondadori et al, 2007) and between different prion protein genotypes (Buchmann et al, 2008). Our sample is homogenous with respect to age, education, and memory performance.…”
Section: Subjectsmentioning
confidence: 99%
“…Education, handedness, and age showed no significant influence on morphology (tested in multiple regression analyses together with TGMV and BDNF genotype) and were therefore not modeled in both analyses. We controlled for SNPs with published influences on brain morphology such as found in the BDNF gene Hariri et al, 2003;Pezawas et al, 2004;Szeszko et al, 2005;Bueller et al, 2006) and 5-HT2a gene (Filippini et al, 2006), and for SNPs with potential influences on morphology such as found in the ApoE gene (Mondadori et al, 2007) and PrnP gene (Papassotiropoulos et al, 2005a), as well as for nonrandom genetic heterogeneity, i.e., hidden, genetic population structure (Papassotiropoulos et al, 2005b). Allelic frequencies of the SNPs with potential influences and the 5-HT2a SNP were not significantly different between the CYP46 genotypes and were not considered further.…”
Section: Statistical Analysesmentioning
confidence: 99%